2007
DOI: 10.1016/j.jde.2007.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Globally Lipschitz continuous solutions to a class of quasilinear wave equations

Abstract: This work investigates the existence of globally Lipschitz continuous solutions to a class of Cauchy problem of quasilinear wave equations. Applying Lax's method and generalized Glimm's method, we construct the approximate solutions of the corresponding perturbed Riemann problem and establish the global existence for the derivatives of solutions. Then, the existence of global Lipschitz continuous solutions can be carried out by showing the weak convergence of residuals for the source term of equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Equation (1.1) appears naturally in the study for liquid crystals [1][2][3][4]. In addition, Chang et al [5], Su [6] and Kian [7] where (x,t) R × R + , u 0 (x),ω 0 (x) R. Furthermore, Nishihara [8] and Hayashi [9] obtained the global solution to one dimension semilinear damped wave equation…”
Section: Introductionmentioning
confidence: 99%
“…Equation (1.1) appears naturally in the study for liquid crystals [1][2][3][4]. In addition, Chang et al [5], Su [6] and Kian [7] where (x,t) R × R + , u 0 (x),ω 0 (x) R. Furthermore, Nishihara [8] and Hayashi [9] obtained the global solution to one dimension semilinear damped wave equation…”
Section: Introductionmentioning
confidence: 99%
“…consider (1.5)), although we avoid the resonance, but we face the difficulty that the term ∂G/∂U of (1.5) does not satisfy the conditions described in [6,8,15,30]. To overcome the above difficulties, we recently considered the Cauchy problem of (1.1) with more general flux, and proved the existence of globally Lipschitz continuous solution by applying the Lax's method and generalized Glimm's method, see [4]. More precisely, we modify the original Riemann problem into a perturbed Riemann problem.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the work [4], we consider the initial-boundary value problem (1.1) in this article. Unfortunately, due to the boundary condition, the method of [4] for the construction of approximate solutions near the boundary layer cannot be applied directly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method in [18] showed that incorporating the source term as a wave gave sharp time independent bounds for solutions of the initial value problem, while the operator-splitting method gave only time dependent bounds in this nonstrictly hyperbolic setting. Recently, this framework was extended to quasi-linear wave equations [4,14,29],…”
mentioning
confidence: 99%